Modeling Transmission Lines With Open Boundaries via Infinite Mapping Layer - Gines Garcia-Contreras; Juan Corcoles; Jorge A. Ruiz-Cruz; Matteo Oldoni; Lorenzo Codecasa; Gian Guido Gentili (IEEE Journal of Microwaves, 2024)
In this paper we introduce the use of several different Infinite Mapping Layers to model open boundaries in the 2-D Finite Element Method for the computation of transmission line parameters. The transformation maps a semi-infinite interval to a finite interval, thereby providing a simple and accurate description of open boundaries while keeping the size of the computational domain very compact. The method has been evaluated and tested on a variety of common transmission line geometries appearing in the literature and its accuracy is validated by comparing the results with canonical cases having closed expressions and with arbitrary geometries computed with commercial software tools. Various geometrical transformations have been developed and tested, and their performances evaluated in terms of accuracy and efficiency. Finally, the possibility of using a radial Infinite Mapping Layer has also been considered.